Aggressiveness in Adolescents Aged 15-18 Years Old, Under the Influence of Social Environment and the Introduction of New Technologies in Every Day Life - Lamcja, Flora; ZEQAJ, Armando (European Journal of Multidisciplinary Studies, 2016)
Aggressiveness in Adolescents Aged 15-18 Years Old, Under the Influence of Social Environment and the Introduction of New Technologies in Every Day Life